Progression to hypertension in youth and young adults with type 1 or type 2 diabetes: The SEARCH for Diabetes in Youth Study. Issue 5 (15th April 2020) - Koebnick, Corinna; Imperatore, Giuseppina; Jensen, Elizabeth T.; Stafford, Jeanette M.; Shah, Amy S.; Mottl, Amy K.; Bell, Ronny A.; Dabelea, Dana; Liese, Angela D.; Marcovina, Santica M.; D'Agostino, Ralph B.; Urbina, Elaine M.; et al.
Abstract: Central obesity may contribute to the development of hypertension in youths with diabetes. The SEARCH for Diabetes in Youth Study followed 1518 youths with type 1 diabetes (T1D) and 177 with type 2 diabetes (T2D) diagnosed when <20 years of age for incident hypertension. Incident hypertension was defined as blood pressure ≥95th percentile (or ≥130/80 mm Hg) or reporting antihypertensive therapy among those without hypertension at baseline. Poisson regression models were stratified by diabetes type and included demographic and clinical factors, clinical site, and waist‐to‐height ratio (WHtR). Youths with T2D were more likely to develop hypertension than those with T1D (35.6% vs 14.8%, P < .0001). For each 0.01 unit of annual increase in WHtR, adjusted relative risk for hypertension was 1.53 (95% CI 1.36‐1.73) and 1.20 (95% CI 1.00‐1.43) for youths with T1D and T2D, respectively. Effective strategies targeted toward reducing central obesity may reduce hypertension among youths with diabetes.